A Comprehensive Review on the Synergy between Emergency Services, Nurses, Assistant Nurses, and Laboratory Teams in Critical Care - Alsharari, Sultan Mohammed F; Al-Sharari , Hani Subaih B; Awad , Doaa Ali; Alsharari , Nedal Lahii; Alsharari , Yousef Salamah; Alyami , Saeed Hadhir; Sofyani , Ali Abdulrhman A; Khawaji , Majdi Mohammed I; Khiswi , Abdullah Ali M; Alzahrani , Rayan Khalid A; Alanazi , Mahmoud Mohammed; Alharbi , Abdulrahman Owaidh A; et al. (Journal of Ecohumanism, 2024)
Emergency services as well as the nurses, assistant nurses and the laboratory teams, must work hand in hand when providing critical care. In critically-acclaimed cases where time is of the essence, interdisciplinary coordination enhances the diagnosis, delivery of treatments and patient outcomes. The emergency patient is kept safe, rapidly moved, and treated by triage and early care, followed by ward nurses and assistant nurses who can perform continuous observations, supported by laboratory personnel who provide essential information needed for treatment. However, collaboration is often faced with barriers such as communication breakdown, organizational structure, and lack of standard use of technology. Works released between 2010 and 2020 indicate that standardization of information transfer, such as the SBAR model, and embracing clinical information technology, such as EHR, improves team coordination, minimizes adverse events, and shortens reaction time. Also, interdisciplinary training is another important practice that helps ensure that different departments have enough trust for one another, enabling better integration. Since the changes in attitudes towards interdisciplinary collaboration, new technologies such as data sharing and diagnostics have enhanced the flow of information between teams. However, the patchy implementation throughout facilities has hindered this. Other areas that may need to be tackled to improve collaboration and support these initiatives include workload disparities, the number of staff, and other resources available to research and analyse different topics. This review systematically presents data regarding the collaboration of these teams. It highlights the implementation of common processes and information exchange in Main Communication Protocols and effective workflow for coordinating the care for critically ill patients as pillars for better outcomes in patient care in critical care settings.